Chapter 3 Use of Bioinformatics in Planning a Protein Purification - Burgess, R.R.
Now that many hundreds and even thousands of whole genomes have been sequenced, it is rare to be studying a target protein whose amino acid sequence is not known. However, it is still often necessary to obtain large amounts of the target protein for a variety of purposes including structural studies, drug discovery, enzymology, protein biochemistry, and industrial application. It would seem that knowing the amino acid sequences would make it much easier to design an effective purification of that protein. We examine in this chapter what you can and cannot predict from an amino acid sequence and conclude that protein purification is still largely an empirical science. © 2009 Elsevier Inc. All rights reserved
Keywords: AMINO ACID SEQUENCE; BIOINFORMATICS; ENZYMOLOGY; GENE SEQUENCE; GENOME; PRIORITY JOURNAL; PROTEIN ANALYSIS; PROTEIN PURIFICATION; PROTEIN STRUCTURE; REVIEW; ALGORITHM; ANIMAL; BIOLOGY; CHEMISTRY; HUMAN; HUMAN; METABOLISM; METHODOLOGY; PHYSIOLOGY; PROTEIN CONFORMATION; PROTEIN DENATURATION; PROTEIN MULTIMERIZATION; PROTEIN PROCESSING